Energy efficiency enhancement of a single mixed refrigerant LNG process using a novel hydraulic turbine. (1st February 2018) - Qyyum, Muhammad Abdul; Ali, Wahid; Long, Nguyen Van Duc; Khan, Mohd Shariq; Lee, Moonyong
Abstract: The advancement in hydraulic turbine (HT) technology was exploited for energy and cost benefits in natural gas liquefaction. Replacing the conventional Joule–Thompson (JT) valve with HT has the potential to recover the work input. This research investigated the effect of replacing the JT valve with HT in the energy efficiency enhancement of a single mixed refrigerant (SMR) process. To fully take the potential benefit of the HT, the proposed SMR schemes were optimized by using a modified coordinate descent optimization method, which was implemented in Microsoft Visual Studio environment and linked to the rigorous HYSYS ® model. The results showed that the required energy of the proposed HT based SMR process could be saved up to 16.5% in comparison with the conventional SMR process using the JT valves. Utilization of the recovered energy into boosting the natural gas feed pressure could further reduce the energy requirement up to 25.7%. Exergy efficiency analysis also showed that whole exergy efficiency of the enhanced SMR process can be increased by about 11% as compared to the base case. The proposed HT based liquefaction technology can be extended to other natural gas liquefaction processes as an attractive option for enhancing the energy efficiency. Highlights: An enhanced SMR process using hydraulic turbines was proposed for improving energy efficiency. Synergistic effects by hydraulic turbines with optimization were investigated. The proposed SMR process reduces energy requirement up to 16.5%. Efficient utilization of recovered energy further reduces energy requirement up to 25.7%. The proposed hydraulic turbine based liquefaction can be extended to other natural gas liquefaction processes.